Lean marketing and its role in achieving the competitive advantage of the bank: An analytical exploratory study of the opinions of a sample of workers in private banks, the holy city of Karbala - Abbas Al-Janabi, Adel; Murad Kazem, Mohammed (Iraqi Journal for Administrative Sciences, 2024)
This research aims to determine the impact of the Lean marketing system on the competitive advantage in some Iraqi private banks, as the research attempted to provide a theoretical framework for the most important topics presented by writers and researchers on research variables as well as an analytical practical framework for the views of a selected sample within the research community that included administrative leaders in banks (managers) Banks, their assistants, department heads, and people’s heads) The sample size reached (100) persons and represented the independent variable by Lean marketing in its six dimensions (reducing excessive marketing operations, reducing waiting time, reducing excessive processing, reducing unnecessary movements, reducing the brain Defective marketing requests, stimulating the untapped talent and creativity of workers) and the approved variable is the competitive advantage in its four dimensions (cost, quality, flexibility, delivery). The research reached a set of conclusions, the most important of which (the main and subsidiary hypotheses related to the research were validated by the existence of a correlation and impact between the variables of the research). As for the most important recommendations (the need to take care of spreading the culture of eliminating waste in all its forms among workers in the various productive and service organizations, especially banking ones).